Review—Status of Zinc-Silver Battery. Issue 13 (1st January 2019) - Le, Shiru; Zhang, Lijun; Song, Xueqin; He, Shaofei; Yuan, Zaifang; Liu, Fuliang; Zhang, Naiqing; Sun, Kening; Feng, Yujie
Abstract : As the capacity reach as high as 350 Wh·kg −1 and 750 Wh·L −1, zinc-silver batteries are widely used in military, aerospace and other fields because of their high specific energy and discharging rate, together with their safety and reliability. In this paper, the researches progresses of silver oxide electrode in eliminating high plateau stage, improving thermal stability and its structure are reviewed. Also the corrosion inhibitor of zinc electrode to prevent hydrogen evolution is summarized. In addition, the technical progress of battery separator is presented. The developing trends of the zinc silver battery are prospected.